2019
DOI: 10.3389/fimmu.2018.03124
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIIb Restricts Antibody-Dependent Destruction of Cancer Cells by Human Neutrophils

Abstract: The function of the low-affinity IgG-receptor FcγRIIIb (CD16b), which is uniquely and abundantly expressed on human granulocytes, is not clear. Unlike the other Fcγ receptors (FcγR), it is a glycophosphatidyl inositol (GPI) -anchored molecule and does not have intracellular signaling motifs. Nevertheless, FcγRIIIb can cooperate with other FcγR to promote phagocytosis of antibody-opsonized microbes by human neutrophils. Here we have investigated the role of FcγRIIIb during antibody-dependent cellular cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 70 publications
8
104
0
Order By: Relevance
“…In addition, the contribution of neutrophils, the most abundant type of granulocytes, and the role of CD16B in tumor control is not fully understood. 78,79 Therefore, it is suggested that also those patients with a low affinity CD16A genotype (158F, roughly 85% of the Caucasian population) 74,75 will respond better to immune cell engagers based on the ROCK® anti-CD16A domains. Moreover, the lack of binding to Fc receptors other than CD16A could substantially reduce sink-effects compared to conventional mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the contribution of neutrophils, the most abundant type of granulocytes, and the role of CD16B in tumor control is not fully understood. 78,79 Therefore, it is suggested that also those patients with a low affinity CD16A genotype (158F, roughly 85% of the Caucasian population) 74,75 will respond better to immune cell engagers based on the ROCK® anti-CD16A domains. Moreover, the lack of binding to Fc receptors other than CD16A could substantially reduce sink-effects compared to conventional mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…The FcgRIIIb-specific 11.5 blocking antibody, actually enhanced FcgRI up-regulation, as did PI-PLC, a FcgRIIIb-specific shedding enzyme. Moreover, the 3G8 blocking antibody (36), which does not discriminate between the two FcgRIII isoforms, did not affect FcgRI up-regulation, supporting the concept of a decoy role for that receptor (10,37,38). Results leave the possibility of a role for FcgRIIIa.…”
Section: Discussionmentioning
confidence: 77%
“…The FcgRIIIb-specific 11.5 blocking antibody, actually enhanced FcgRI upregulation, as did PI-PLC, a FcgRIIIb-specific shedding enzyme. Moreover, the 3G8 blocking antibody, 57 which does not discriminate between the two FcgRIII isoforms, did not affect FcgRI upregulation, supporting the concept of a decoy role for FcgRIIIb 12,58,59 in this process. Results leave the possibility of a role for FcgRIIIa.…”
Section: F I G U R Ementioning
confidence: 77%